Community policing and crime reduction: A case study at Korogwe district, Tanga, - Hassani, Haruna M (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirements for the award of the degree of Master of Science in Human Resource Management of Mzumbe University